1998
DOI: 10.1046/j.1365-2508.1998.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of abnormal uterine bleeding in postmenopausal patients using hormone replacement therapy

Abstract: Objective To investigate the cause of uterine bleeding in menopausal patients using hormone replacement therapy (HRT), and the efficacy of resectoscopic surgery for treatment of irregular vaginal bleeding caused by benign uterine pathology in such patients. Design Retrospective case series. Setting Endoscopy unit of a private urban hospital. Subjects 143 patients receiving HRT and with irregular vaginal bleeding, examined between January 1994 and December 1997. Interventions All the patients were evaluated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The high incidence of endometrial polyps in tibolone users which was seen in the present study confirms previous observations carried out with hysteroscopy; these revealed that the presence of uterine intracavitary lesions accounts for a large number of the bleeding episodes reported during tibolone treatment 5,6 . The higher incidence of endometrial polyps in menopausal patients using HRT has also been observed in previous studies 8,10 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high incidence of endometrial polyps in tibolone users which was seen in the present study confirms previous observations carried out with hysteroscopy; these revealed that the presence of uterine intracavitary lesions accounts for a large number of the bleeding episodes reported during tibolone treatment 5,6 . The higher incidence of endometrial polyps in menopausal patients using HRT has also been observed in previous studies 8,10 …”
Section: Discussionsupporting
confidence: 92%
“…The discrepancy between biopsy and hysteroscopic findings may be caused by the inability of blind endometrial biopsies to correctly identify polyps and submucous myomas in the majority of patients 7 . In fact, in menopausal patients who were experiencing abnormal uterine bleeding during HRT, the diagnosis of endometrial polyp was missed by endometrial biopsy in most cases 8 …”
Section: Introductionmentioning
confidence: 99%
“…Irregular bleeding associated with the use of a combination of oestrogens and progestogens is considered as an unacceptable side effect of HRT [7]. In continuous combined regimens, oestrogens and progestogens are administered together daily, and such treatment should produce an atrophic endometrium and amenorrhoea.…”
Section: Introductionmentioning
confidence: 99%